Precipitation of salts in freezing seawater and ozone depletion events: a status report - S. Morin; G. M. Marion; R. von Glasow; D. Voisin; J. Bouchez; J. Savarino (Copernicus Publications, 2008)
In springtime, the polar marine boundary layer exhibits drastic ozone depletion events (ODEs), associated with elevated bromine oxide (BrO) mixing ratios. The current interpretation of this peculiar chemistry requires the existence of acid and bromide-enriched surfaces to heterogeneously promote and sustain ODEs. Sander et al. (2006) have proposed that calcium carbonate (CaCO 3 ) precipitation in any seawater-derived medium could potentially decrease its alkalinity, making it easier for atmospheric acids such as HNO 3 and H 2 SO 4 to acidify it. We performed simulations using the state-of-the-art FREZCHEM model, capable of handling the thermodynamics of concentrated electrolyte solutions, to try to reproduce their results, and found that when ikaite (CaCO 3 ·6H 2 O) rather than calcite (CaCO 3 ) precipitates, there is no such effect on alkalinity. Given that ikaite has recently been identified in Antarctic brines (Dieckmann et al., 2008), our results show that great caution should be exercised when using the results of Sander et al. (2006), and reveal the urgent need of laboratory investigations on the actual link(s) between bromine activation and the pH of the surfaces on which it is supposed to take place at subzero temperature. In addition, the evolution of the Cl/Br ratio in the brine during freezing was computed using FREZCHEM, taking into account Br substitutions in Cl–containing salts.